The Chinese advisory groups in the first Indochina War: their formation, evolution, and disbandment. Issue 2 (3rd April 2022) - Cheng, Xiaohe
ABSTRACT: The Communist Party of China swiftly embarked on its first overseas mission by sending military advisors to Vietnam right after founding the People's Republic of China in 1949. By relying on first-hand archival materials and interviews with former advisors, this study reveals the formation, evolution, and disbandment of the Chinese advisory groups in Vietnam, the details of which remain generally vague, if not unknown, to the academic community. Thus, the study works to uncover the historical facts that can explain the rise and fall of these groups that operated in Vietnam from 1950–56.